2022
DOI: 10.22515/finalmazawa.v2i2.4425
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Pembiayaan Bankziska Terhadap Praktik Riba Pada Pelaku Umkm

Abstract: The problem of poverty and social inequality has become an acute social problem in this country. From the era of the kingdom, colonialism, to the era of independence as it is today, there are still many Indonesian people who are trapped in poverty. A decent and prosperous life is still a dream and hope that has not yet been realized. Thus, of course, a precise and accurate formulation is needed to minimize the poverty rate. It is explained that usury referred to in the Qur'an as a thing that has the nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
0
0
2
Order By: Relevance
“…Program pembebasan riba untuk masyarakat tersebut, Bankziska Lazismu menggandeng BMT Hasanah sebagai partner dalam program ini. Selanjutnya dinamakan dengan Bantuan Keuangan Berbasis Zakat, Infaq, Shodaqoh dan Dana Sosial Keagamaan Lainnya, yang disingkat BANKZISKA (Setiawan et al, 2021).…”
Section: Sejarah Bankziska Dan Latar Belakangunclassified
“…Program pembebasan riba untuk masyarakat tersebut, Bankziska Lazismu menggandeng BMT Hasanah sebagai partner dalam program ini. Selanjutnya dinamakan dengan Bantuan Keuangan Berbasis Zakat, Infaq, Shodaqoh dan Dana Sosial Keagamaan Lainnya, yang disingkat BANKZISKA (Setiawan et al, 2021).…”
Section: Sejarah Bankziska Dan Latar Belakangunclassified
“…Beberapa lembaga resmi yang menawarkan pembiayaan hutang dengan berbagai persyaratan yang merepotkan membuat sebagian pelaku UMKM lebih memilih untuk menggunakan pembiayaan yang tidak resmi, seperti melalui rentenir. Persyaratan pinjaman hutang kepada retenir lebih mudah dibandingkan lembaga resmi (Setiawan, 2022). Hal ini menjadi akar masalah yang serius dikerenakan para pelaku pedagang yang meminjam kepada pihak renternir akan terjerat dengan bunga yang begitu tinggi (Suma, 2017).…”
Section: Pendahuluanunclassified
“…In subsequent research it was found that the effectiveness of BankZiska has been able to reduce the number of moneylenders who ensnare their partners by 38% and liberate 20% of their partners from loan sharks (Futaqi, Susanti, & Ulya, 2022). In addition, research on BankZiska conducted by Setiawan, et. al (Setiawan, Sholikha, Rahayu, & Fitrianna, 2021) concluded that the existence of BankZiska provides many significant benefits to MSMEs.…”
Section: Introductionmentioning
confidence: 99%